Isolation, Characterization, and Genetic Diversity of Ice Nucleation Active Bacteria on Various Plants - DIANA ELIZABETH WATURANGI; AMELIA TJHEN (HAYATI Journal of Biosciences, 2009)
Ice nucleation active (INA) bacteria is a group of bacteria with the ability to catalyze the ice formation at temperature above -10 oC and causing frost injury in plants. Since, most of the literature on INA bacteria were from subtropical area, studies of INA bacteria from tropical area are needed. We sampled eight fruits and 36 leaves of 21 plant species, and then identified through biochemical and genetic analysis. INA bacteria were characterized for INA protein classification, pH stability, and optimization of heat endurance. We discovered 15 INA bacteria from seven plants species. Most of bacteria are oxidase and H2S negative, catalase and citrate positive, gram negative, and cocoid formed. These INA bacteria were classified in to three classes based on their freezing temperature. Most of the isolates were active in heat and pH stability assay. Some isolates were analysed for 16S rRNA gene. We observed that isolates from Morinda citrifolia shared 97% similiarity with Pseudomonas sp. Isolate from Piper betle shared 93% similarity with P. pseudoalcaligenes. Isolate from Carica papaya shared 94% similarity with Pseudomonas sp. While isolate from Fragaria vesca shared 90% similarity with Sphingomonas sp. Key words: INA bacteria, isolation, characterization, genetic diversity, plants